THE IMPACT OF MUSIC THERAPY SESSIONS ON CHILDREN DIAGNOSED WITH PROGRESSIVE CHRONIC ILLNESS – A PILOT PROGRAM - Lois VĂDUVA; Annamaria BALLA (Studia Universitatis Babeş-Bolyai. Musica, 2018)
This research proposes to analyse the impact that music therapy sessions had on children diagnosed with progressive chronic illness. During a period of nine months, a group of twenty children benefitted from music therapy sessions that were conducted using improvisation, passive listening, rhythmic grounding and composition. Each music therapy session was prepared with a procedure plan that had specific goals and objectives, depending of the child’s age, temperament, diagnosis and needs. In order to analyse the results of these sessions, clinical observation sheets were filed at the beginning and the end of each session and this paper aims to present the results of this research. The observation sheets included three main domains: facial expression, behaviour and emotions, all with different components that are important in evaluating a child’s response to the therapy. An important finding was that fear, agitation and fury formed a triad, being dependent on each other. Also, the variable of joy seemed to have the most impact, as it was central to other variables such as: touch, look, eye brightness, language, position of the body and position of the head. The results of this pilot program indicate the music therapy has a positive impact on children with progressive chronic illness and it should be further developed and implemented in other parts of the country.